Spatiotemporal behavior of high dominant frequency during paroxysmal and persistent atrial fibrillation in the human left atrium. - Jarman,JW; Wong,T; Kojodojojo,P; Sophr,H; Davies,JE; Roughton,M; Francis,DP; Kanagaratnam,P; Markides,V; Davies,DW; Peters,NS (Circ Arrhythm Electrophysiol., 2012)
BACKGROUNDSites of high dominant frequency (DF(peak)) are thought to indicate the location of drivers of atrial fibrillation (AF), but characterization of their spatiotemporal distribution and stability, critical to their relevance as targets for catheter ablation, requires simultaneous global mapping of the left atrium.METHODS AND RESULTS:Noncontact electrograms recorded simultaneously from 256 left atrial sites during spontaneous AF were analyzed. After subtraction of the ventricular component, fast Fourier transform identified the DF at each site. Focal areas of DF(peak) were defined as those having a DF >20% above all neighboring sites. Twenty-four patients with spontaneous AF (11 paroxysmal and 13 persistent) were studied. In paroxysmal AF, sites of DF(peak) (mean DF, 11.6±2.9 Hz) were observed in 100% of patients (present during 65% of the mapping period). In contrast, DF(peak) was detected in only 31% of patients with persistent AF (P<0.001) and for only 5% of the mapping period (P<0.001). In both groups, locations of DF(peak) varied widely in both consecutive and separated segments of AF (κ coefficient range, -0.07-0.22). Activation sequences around sites of DF(peak) did not demonstrate centrifugal activation that would be expected from focal drivers.CONCLUSIONS:Focal areas of high DF are more frequent in paroxysmal than persistent AF, are spatiotemporally unstable, are not the source of centrifugal activation, and are not, therefore, indicative of fixed drivers of AF. In the absence of spatiotemporal stability, the success of ablation at sites of DF(peak) cannot be explained by elimination of fixed drivers.